2020
DOI: 10.1098/rsbl.2020.0124
|View full text |Cite
|
Sign up to set email alerts
|

Condition dependence of phenotypic integration and the evolvability of genitalic traits in a neriid fly

Abstract: The spectacular diversity of insect male genitalia, and their relative insensitivity to the environment, have long puzzled evolutionary biologists and taxonomists. We asked whether the unusual evolvability of male genitalia could be associated with low morphological integration of genitalic traits, by comparison with male somatic traits and female traits. We also asked whether this pattern was robust to variation in resource availability during development, which affects adult condition. To address these quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Despite much recent progress on this topic (Pigliucci & Preston, 2004; Schlosser & Wagner, 2004), most empirical studies have only studied patterns of phenotypic integration in a single environment (Pigliucci & Preston, 2004); but see (Liu et al., 2007; Pigliucci et al., 1995). In this study, we found an increase in coefficient of integration (CI) with density at 50 days, consistent with some studies (Gianoli, 2004; Schlichting, 1986; Wylde & Bonduriansky, 2020), suggesting the strength of phenotypic integration can increase with environmental stresses (García‐Verdugo et al., 2009; Gianoli, 2004; Schlichting, 1989a,b; Waitt & Levin, 1993). The increase in the number and strength of correlations among functionally correlated traits (phenotypic integration) is related to the extent of environmental stress (Gianoli, 2004; Schlichting, 1986) and endow plants the ability to effectively respond to such stress (Chapin III, 1991).…”
Section: Discussionsupporting
confidence: 91%
“…Despite much recent progress on this topic (Pigliucci & Preston, 2004; Schlosser & Wagner, 2004), most empirical studies have only studied patterns of phenotypic integration in a single environment (Pigliucci & Preston, 2004); but see (Liu et al., 2007; Pigliucci et al., 1995). In this study, we found an increase in coefficient of integration (CI) with density at 50 days, consistent with some studies (Gianoli, 2004; Schlichting, 1986; Wylde & Bonduriansky, 2020), suggesting the strength of phenotypic integration can increase with environmental stresses (García‐Verdugo et al., 2009; Gianoli, 2004; Schlichting, 1989a,b; Waitt & Levin, 1993). The increase in the number and strength of correlations among functionally correlated traits (phenotypic integration) is related to the extent of environmental stress (Gianoli, 2004; Schlichting, 1986) and endow plants the ability to effectively respond to such stress (Chapin III, 1991).…”
Section: Discussionsupporting
confidence: 91%
“…We utilized a morphometric dataset on the neriid fly Telostylinus angusticollis that included 22 somatic and genitalic traits measured on individuals reared on nutrient-rich and nutrient-poor larval diets (Wylde & Bonduriansky, 2020). Eggs collected from stock flies were reared using a larval diet that is intermediate in nutrient concentration between the rich and poor diets, based on Sentinella et al (2013).…”
Section: Study Systemmentioning
confidence: 99%
“…Despite much recent progress on this topic (Pigliucci & Preston, 2004;Schlosser & Wagner, 2004), most empirical studies have only studied patterns of phenotypic integration in a single environment (Pigliucci & Preston, 2004; but see Liu et al, 2007;Pigliucci et al , 1995). In this study, we found an increase in coefficient of integration (CI) with density at 50 d (Gianoli, 2004;Schlichting, 1986;Wylde & Bonduriansky, 2020), and decrease in the number of correlations (NC) with density at 70 d (Badyaev et al , 2005;Mallitt et al , 2010;Pigliucci & Kolodynska, 2002). The stage-dependence responses in CI suggested the strength of response of integration to density decreased over time.…”
Section: Phenotypic Integrationmentioning
confidence: 62%